O anticomunismo fardado : um estudo sobre representações anticomunistas, intervenção e repressão na Polícia Militar de Minas Gerais (1947 – 1954) - André Gustavo da Silva (2017)
This research aims to investigate the process of formation and development of anti-Communist representations in the military police of Minas Gerais. Raise the thesis that these anti-Communist representations, contrary to what would have happened in the armed forces, notably in the Brazilian Army, would not have arisen, on military police of Minas Gerais from the events that marked the Attempted Communist of 1935. In spite of this revolutionary movement have been responsible for the formation of anti-Communist representations in the army, we believe that such events do not impacted in the same way the PMMG. However, we assumed that the repression that followed an uprising, triggered by the repressive apparatus of the State, against the Communists, caused roughly the organic restructuring of the Brazilian Communist Party. This restructuring aimed at, among other things, allow the return of political and partisan activities of the members of the PCB with the working classes, participation, this hindered by almost ten years of hiding the party off submitted after an uprising. One of the measures adopted by the Brazilian Communist Party, in sit back to the orientation of the action of the working classes was enter your in various spheres of the militant world of work, in order to indoctrinate and co-opt new supporters to the ranks of the PCB. In Minas Gerais the party would have promoted the insertion of its militants in several occupational categories, civilian and military, as we shall see. One of these categories was the military police of Minas Gerais, whose Command would have identified the presence of Communist militants in his paintings from 1947. This left wing political militancy of some military police was immediately identified as a conspiratorial, "infiltration" of the communist doctrine, in barracks that force to supposedly destroy the principles of hierarchy and discipline, as part of the preparations in which the revolutionary Communists would be supposedly committed. Subject to the foregoing, the intent of this work was to investigate the set of circumstances that led to the formation and development of anti-Communist representations in the political thought of the military police of Minas Gerais, from the alleged allegations of infiltration Communist in his paintings.